2011
DOI: 10.1016/j.bpj.2011.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Shear Stress Regulates Adhesion and Rolling of CD44+ Leukemic and Hematopoietic Progenitor Cells on Hyaluronan

Abstract: Leukemic cells and human hematopoietic progenitor cells expressing CD44 receptors have the ability to attach and roll on hyaluronan. We investigated quantitatively the adhesion behavior of leukemic cell lines and hematopoietic progenitor cells on thin films of the polysaccharides hyaluronan and alginate in a microfluidic system. An applied flow enhances the interaction between CD44-positive cells and hyaluronan if a threshold shear stress of 0.2 dyn/cm(2) is exceeded. At shear stress ∼1 dyn/cm(2), the cell rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 61 publications
6
52
1
Order By: Relevance
“…It should be mentioned that the rolling behaviors are not identical between the cells expressing CD44 and the beads displaying the HABD. For instance, the stabilization of the rolling (e.g., increase of adhesion numbers or decrease of rolling velocities) at high shear stress was observed only for the experiments using cells (21,23). Those differences may be ascribed to the cellular features, such as the formation of microvilli, slings (26), and cell flattening, which also contribute to stable rolling (27).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It should be mentioned that the rolling behaviors are not identical between the cells expressing CD44 and the beads displaying the HABD. For instance, the stabilization of the rolling (e.g., increase of adhesion numbers or decrease of rolling velocities) at high shear stress was observed only for the experiments using cells (21,23). Those differences may be ascribed to the cellular features, such as the formation of microvilli, slings (26), and cell flattening, which also contribute to stable rolling (27).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, it was reported that the rolling of CD44-expressing cells is enhanced at the higher shear stress (23), raising the possibility that CD44 possesses some mechanochemical specializations to resist higher tensile force. Considering the fact that the C terminus of CD44 HABD is connected to the plasma membrane, the force applied from the C terminus of HABD would induce the allosteric transition from the O to the PD state, thereby providing the resistance to the applied force.…”
Section: E7304-e7305mentioning
confidence: 99%
“…It has been reported that the strength of the biofilms would decrease when the cell viability in the biofilms reduced [52][53][54]. Thus, the potential mechanism for the biofilm inhibition effect in this study is that thermal shock caused disintegration of the bacterial cell membrane and killed the cells in the biofilms.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore this new assay revealed that cell removal from directed nanostructures depends on the flow direction [23] and that CD44? leukemic cells attach to hyaluronans by a catch bond activated binding [24].…”
Section: Introductionmentioning
confidence: 99%